DIVERSIFIKASI KONSUMSI PANGAN RUMAH TANGGA PEDESAAN DAN PERKOTAAN (STUDI KASUS KECAMATAN PANJI KABUPATEN SITUBONDO) - Gema Iftitah A Yekti; Yasmini Suryaningsih (Relawan Jurnal Indonesia, 2017)
The aims of this study to analyze the consumption patterns in the urban and rural household, and also analyzed the dietary diversity of the urban and rural household. The method to collect data used food recall 2x24 hours method. The consumption pattern was analyzed by Recommended Dietary Allowances (RDA). Diversification food consumption analyse used dietary diversity. Analysis result showed consumption patterns in the urban and rural household still not differ yet and tend to depend on one kind of food, so consumption of energy still under recommended of RDA. Consumption of energy and protein in urban is 1514,18 kcal and 40,06 g. Consumption of energy and protein in rural is 1567,77 kcal and 37,58 g. Group of food match with RDA and even more there are in group of sugar for urban area and group of oil, fat and sugar for rural area. Implementtion of diversification food consumption in urban area and rural area still not match with Dietary Diversity Score (DDS) rate for urban 57,50 and rural 50,15.